2014
DOI: 10.1016/j.jvs.2014.01.062
|View full text |Cite
|
Sign up to set email alerts
|

The current position of precuffed expanded polytetrafluoroethylene bypass grafts in peripheral vascular surgery

Abstract: ASV bypasses are still the first-choice conduit in peripheral bypass surgery performed in patients with PAD. Precuffed ePTFE bypasses are acceptable alternatives in the absence of adequate autologous vein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 24 publications
0
15
0
2
Order By: Relevance
“…30 Delirium In our hospital, several studies before implementation of the DHPSP have been performed. A study by van der Slegt et al 31 reported a delirium incidence of 3% in patients receiving peripheral vascular surgery. This study, performed in 2012, reported a lower incidence rate on delirium compared with this study.…”
Section: Discussionmentioning
confidence: 99%
“…30 Delirium In our hospital, several studies before implementation of the DHPSP have been performed. A study by van der Slegt et al 31 reported a delirium incidence of 3% in patients receiving peripheral vascular surgery. This study, performed in 2012, reported a lower incidence rate on delirium compared with this study.…”
Section: Discussionmentioning
confidence: 99%
“…In this report, we demonstrate the effectiveness of SLIPS-modified biomedical implants to resist device-associated infection after bacterial challenge in vivo. Expanded polytetrafluoroethylene (ePTFE) was selected as a model material given its prevalent use in clinical care in the form of prosthetic hernia meshes [36-38], grafts for cardiovascular reconstruction [39, 40], and as alloplastic implants in cosmetic and reconstructive surgery [41-43], as well as its known susceptibility to infection [44, 45]. As a porous, fluorinated implant material, ePTFE is readily amenable to infusion with fluorinated lubricants, such as perfluoropolyether (PFPE), perfluoroperhydrophenanthrene (PFPH), and perfluorodecalin (PFD).…”
Section: Introductionmentioning
confidence: 99%
“…During the 5-year follow-up, the patency rate with ASV was better than with PTFE grafts (82% vs. 26%, p<0.05). 6 ) Surgical bypass with PTFE should therefore be limited to patients with no other revascularization option. Meanwhile, the operative mortality is highly variable, which can range from 1.3% to 6.3%, which largely depends on cardiovascular risk, and should be considered preoperatively.…”
mentioning
confidence: 99%